Evaluation of Perception of II Year MBBS Students Regarding A Clinical Forensic Medicine Module in a Tertiary Care Centre (Medico Legal Update, 2020)
Background: Besides providing treatment to patients in medico legal cases, a competent medical practitioneris legally bound to collect all necessary evidence material from the body of patients which may help in theinvestigation of the crime and to aid in the court of law towards justice. In India, the current practice oftheoretical teaching of students in Forensic Medicine towards handling medicolegal cases is not enough todeliver clinical skills effectively in handling medico-legal cases.Aims & Objectives: This study was undertaken with objectives to evaluate students perception on ClinicalForensic Medicine and impart them a hands on training towards handling antemortem medico legal cases.Material & Method: It was an educational interventional study, including 125 second MBBS undergraduatestudents. At the end of module, the students’ responses towards educational project on Clinical ForensicMedicine were collected in the form of a pre-validated questionnaire template.Results & Conclusion: About 52 % students responded as agreed and 29 % strongly agreed with thequestionnaires at the end of this module. Students favoured Clinical Forensic Medicine Module as aneffective teaching/learning method to learn on the basics of handling medico legal cases.